The Principle of Social Justice As a Solution in Illegal Mining Activities in The Old Wells Oil Management - Lego Karjoko; I Gusti Ayu Ketut Rachmi Handayani; Abdul Kadir Jaelani; Willy Naresta Hanum (Justitia Jurnal Hukum, 2021)
The old wells oil management is petroleum management which accentuates the empowerment of local communities in the producing region. The goal of this oil management is to provide maximum prosperity for the people as mandated by Article 33 of the 1945 Constitution. This paper aims to formulate the model of old wells oil management based on the social justice principle. This paper has a normative legal study method that uses a term of old wells management in Wonocolo oil fields, Bojonegoro regency. The result is because old wells oil management in Wonocolo oil field does not fully reflect the social justice principle, then it causes illegal mining activities. Therefore, it is necessary to formulate a model of old wells management based on the principle of social justice with two indicators i.e. 1) The equal distribution of benefits and 2) Participation.Keywords: Oil, Old Wells, Illegal Mining, Benefit Distribution, Participation, Social Justice